TARIQ RAMADAN DAN FAHAM BUDAYA ISLAM YANG TOLERAN DAN INKLUSIF - ahmad nabil amir (Kopertais Wilayah III Yogyakarta, 2022)
This paper aims to reflect the progressive ideal of reform of Tariq Said Ramadan (born 1962), an accomplished Muslim reformist dan leading exponent of modern Islam in 21th century and its instrumental impact based on his extensive philosophical writings. It argued that Ramadan was arguably the most influential modernist and its leading proponent in the modern history of Islam. The paper endeavors to analyze his modern ideal as articulated in his works such as What I Believe, Radical Reform, To Be A European Muslim and Western Muslims and the Future of Islam. Aspiring for meaningful realization of reform and inclusivism, it brought forth his perspective on minority Muslim in Europe and highlights its compelling and dynamic influence in modern intellectual discourse of civil Islam. Paul Donnelly in The Washington Post has rightly acclaimed him as “A Muslim Martin Luther”. His profound and discursive thoughts essentially emphasize on radical reform, pluralism and ijtihad (independent thinking), articulating its contextual interpretation and significant meaning. The study is based on qualitative method focusing on descriptive and historical analysis of related works and studies of his principal works. The finding shows that Ramadan has brought forth significant reform in the Muslim world that creatively responds to the present challenge of the western world.